The Study of Gas Emission on Natural Gas Leak Localization - Muthia Elma (INFO-TEKNIK, 2008)
Abstract - The aim of this study is to measure gas emission (CH4 and CO2) coming from natural gas leak localization in the soil. Natural gas is injected into soil in different depths and then analyzed by gas detector and micro gas chromatography to know the values CH4, C2H6, C3H8, C4H10, C5H12, O2, N2 and CO2 which is spread out into soil. When there are leaks in the soil, methane (CH4) will spread out underground. Methanotropic bacteria will use this natural gas as an energy source and transform it into carbon dioxide. The micro gas chromatography data was found that the pipes injected from 20 cm leak are 77.16% CH4 loss in 70cm depth, 73.15% in 50cm depth and 14.08% in 20cm depth. And the pipes injected from 30 cm leak are 20.27% in 30 cm depth and 65.13% in 60 cm depth. Then, the pipes injected from 50 cm leak are 23.40% in 30 cm depth and 47.40% in 60 cm depth. The leak source is in 80 cm depth.